INVESTIGATING THE INFLUENCE OF STUDENT-FACULTY PARTNERSHIP ON STUDENT ENGAGEMENT, ACADEMIC PERFORMANCE, SENSE OF BELONGINGNESS, AND SATISFACTION IN HIGHER EDUCATION - Shang Zhao; Lijung You (Fonseca, Journal of Communication, 2024)
This study analyzes the relationships among student-faculty partnership, student engagement, academic performance, sense of belongingness, and satisfaction in higher education institutes students. Student-faculty partnerships improve educational outcomes, but Chinese higher education need further study. This study examines Chinese educational system linkages and mediating processes to address this gap. This study finds significant gaps in the understanding of student-faculty partnerships and their results by reviewing the literature. A quantitative data from surveys of Chinese university students form students was used in this study. SEM statistical method was used to analyze the data to determine correlations and mediating effects. This study affects educational institutions and policymakers. Student-faculty partnerships positively affect student involvement, academic success, belonging, and higher education satisfaction. Student engagement and sense of belonging influence the association between student-faculty interactions and academic success and satisfaction, respectively. These studies demonstrate how good student-faculty partnerships improve student outcomes and satisfaction in Chinese higher education. The paper adds empirical information and clarifies how these relationships affect crucial educational outcomes.